2009
DOI: 10.1371/journal.pone.0008033
|View full text |Cite
|
Sign up to set email alerts
|

Repression of FLOWERING LOCUS T Chromatin by Functionally Redundant Histone H3 Lysine 4 Demethylases in Arabidopsis

Abstract: FLOWERING LOCUS T (FT) plays a key role as a mobile floral induction signal that initiates the floral transition. Therefore, precise control of FT expression is critical for the reproductive success of flowering plants. Coexistence of bivalent histone H3 lysine 27 trimethylation (H3K27me3) and H3K4me3 marks at the FT locus and the role of H3K27me3 as a strong FT repression mechanism in Arabidopsis have been reported. However, the role of an active mark, H3K4me3, in FT regulation has not been addressed, nor hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 63 publications
7
117
1
4
Order By: Relevance
“…However, genome-wide data in Arabidopsis did not show a general association between H3K4me3 and H3K27me3 (Ha et al, 2011). Despite previous results (Jiang et al, 2008;Carles and Fletcher, 2009;Jeong et al, 2009), our ChIP experiments did not confirm any significant change for H3K4me3 in the clf background either at FT or AG. An increase for this mark was observed in swn clf plants, despite the repression of FT. Lafos et al have recently shown that H3K4me3 levels increase globally in swn clf calli, which may explain why higher levels were detected at the FT locus (Lafos et al, 2011).…”
Section: Chromatin Changes Are Not Key Factors In Determining Ft Spatcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, genome-wide data in Arabidopsis did not show a general association between H3K4me3 and H3K27me3 (Ha et al, 2011). Despite previous results (Jiang et al, 2008;Carles and Fletcher, 2009;Jeong et al, 2009), our ChIP experiments did not confirm any significant change for H3K4me3 in the clf background either at FT or AG. An increase for this mark was observed in swn clf plants, despite the repression of FT. Lafos et al have recently shown that H3K4me3 levels increase globally in swn clf calli, which may explain why higher levels were detected at the FT locus (Lafos et al, 2011).…”
Section: Chromatin Changes Are Not Key Factors In Determining Ft Spatcontrasting
confidence: 99%
“…In animal stem cells, active and repressive chromatin marks are present at the same developmental loci and poise their targets for activation or repression during differentiation (Fisher and Fisher, 2011). In Arabidopsis, bivalent chromatin was demonstrated for FT and FLC (Jiang et al, 2008), and a role of bivalent chromatin in finetuning FLC and FT expression was suggested (Jiang et al, 2008;Carles and Fletcher, 2009;Jeong et al, 2009). However, genome-wide data in Arabidopsis did not show a general association between H3K4me3 and H3K27me3 (Ha et al, 2011).…”
Section: Chromatin Changes Are Not Key Factors In Determining Ft Spatmentioning
confidence: 99%
“…This may explain how ZCN8 expression is maintained in the vascular cells of the mature leaf blade, which are many mitotic generations removed from when id1 was active. Recently, several studies have shown that FT is subject to epigenetic regulation as one of several inputs required for its expression (Jiang et al, 2008;Jeong et al, 2009;Adrian et al, 2010;Yang et al, 2010), but this idea remains to be studied in maize.…”
Section: Genetic Position Of Zcn8 In the Maize Flowering Pathwaymentioning
confidence: 99%
“…There are 21 JUMONJI (JMJ) genes in Arabidopsis, which can be categorized into five groups, namely the KDM5/JARID1, KDM4/JHDM3/ JMJD2, KDM3/JHDM2, JMJD6 and JmjC domain-only group, based on their JmjC domain sequences and domain architectures 22,23 . Members from the same group show similar target specificity for histone modifications [24][25][26][27][28][29][30][31][32] . One of the histone modifications, the repressive PcG-mediated H3K27me3, plays a key role in gene repression and developmental regulation, and is actively and dynamically deposited and removed in plants 33 .…”
mentioning
confidence: 97%